2023
DOI: 10.3390/agronomy13082096
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Analysis Reveals the Gene Loci of Yield Traits under Drought Stress at the Rice Reproductive Stage

Abstract: Drought is an important factor limiting the growth and development of rice and thereby seriously affects rice yield. The problem may be effectively solved by dissecting the drought-resistance mechanism of rice, creating excellent drought-resistant germplasm, and mining new drought-resistant genes. In this study, 305 accessions (189 Xian, 104 Geng, 5 Aus, and 7 Basmati) were used to identify drought-related phenotypes such as grain yield per plant (GYP), grain number per panicle (GNP), panicle number per plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…For improved adaptability in the dry direct seeded rice (DDSR) system, GWAS conducted by (Subedi et al 2019 ) revealed 37 highly significant MTAs for 20 parameters, including plant and root morphological traits, nutrient uptake, yield, and its components in MAGIC population of 5 different parents. Wang et al ) 2023 (, identified 78 SNPs significantly associated with drought tolerance in the 305 accessions, including 15, 33, 17, and 13 SNPs associated with grain number per plant (GYP), grain number per panicle (GNP), panicle number per plant (PNP), and plant height (PH), respectively. All these 78 significant SNPs were tagged to only 42 QTLs distributed on all 12 chromosomes, which agrees with our finding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For improved adaptability in the dry direct seeded rice (DDSR) system, GWAS conducted by (Subedi et al 2019 ) revealed 37 highly significant MTAs for 20 parameters, including plant and root morphological traits, nutrient uptake, yield, and its components in MAGIC population of 5 different parents. Wang et al ) 2023 (, identified 78 SNPs significantly associated with drought tolerance in the 305 accessions, including 15, 33, 17, and 13 SNPs associated with grain number per plant (GYP), grain number per panicle (GNP), panicle number per plant (PNP), and plant height (PH), respectively. All these 78 significant SNPs were tagged to only 42 QTLs distributed on all 12 chromosomes, which agrees with our finding.…”
Section: Discussionmentioning
confidence: 99%
“…The agro-climatic conditions have an impact on the cultivation of rice in all the world's rice-growing regions, and crop improvement has historically been considered as a crucial factor in the selection and evolution of improved rice varieties. Soil salinity and water availability for growing rice are two of the most significant agro-climatic conditions that limit yield, even for the advanced rice cultivars (Bhattacharyya et al 2020 ; Wang et al 2023 ; Zampieri et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Haplotype-based breeding allows breeders to combine alleles for distinct polymorphisms (such as SNPs, insertions/deletions, and other markers or variants) on the same chromosome that are inherited together with a low possibility of contemporaneous recombina-tion [206]. In this method, specific genomic regions associated with desirable traits related to climate resilience in rice, such as drought tolerance, salt tolerance, heat resistance, disease resistance, and improved yield, are targeted [207][208][209][210].…”
Section: Introgression Methods and Gene Pyramiding In Developing Clim...mentioning
confidence: 99%